Konseling Paska Bencana: Tela’ah atas Konsep dan Terapi Post Traumatic Stress Disorder - Effendi Dudy Imanudin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2010)
Helping to client who suffer because of calamity victim  need the different specific paradigm of the public service shapes apllied in conventional approach. Service shape have character as social-psychology, stressing to urgency of socius environment and social system in helping to return psychological condition of post calamity client. The excellent  of this  approach not only in preventive effort, promotive, rehabilitative and liberative., but also based to three ideas as: holistic human, integrated approach, humn caring and encountering nature.